Progressive Muslims approach to Mushkil al-Hadith: a critical evaluation - Zainan Nazri, Nurul Jannah (2020)
Questions on the authenticity of Sunnah have long been of central importance to the study of Islam. Among the crucial points that are fiercely debated in this matter is the issue of textual criticism, which appears to have the effect of discrediting the existing record of Sunnah. This study explains and clarifies the relevance of the classical methodology of hadith text criticism in modern times. By using the case of Progressive Islam as the focal point, it explores the impact of modernity on contemporary Muslims’ attitudes towards religious authorities especially the hadith of the Prophet . It examines the extent to which this so-called “progressive” approach is in line with the classical hadith scholars’ methodology. It assesses the interpretational implications of their approach to mushkil ahadith related to the Islamic belief system (‘aqidah), metaphysical issues (ghaybiyyat) and Muslim social affairs (women and racist issues). In a nutshell, this work provides a significant contribution to the understanding of the attitudes of the modernists in particular the Progressive Muslims towards the Prophetic texts in modern times.